2002
DOI: 10.1074/jbc.m205059200
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Foam Cell Formation with Native Low Density Lipoprotein

Abstract: This investigation has elucidated a mechanism for development of macrophage foam cells when macrophages are incubated with native low density lipoprotein (LDL). LDL is believed to be the main source of cholesterol that accumulates in monocyte-derived macrophages within atherosclerotic plaques, but native LDL has not previously been shown to cause substantial cholesterol accumulation when incubated with macrophages. We have found that activation of human monocyte-derived macrophages with phorbol 12-myristate 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 55 publications
8
121
1
1
Order By: Relevance
“…Increasing LDL concentration resulted in a linear and nonsaturating increase in uptake, which at 250 mg/ml doubled total cellular cholesterol and increased cholesteryl ester level to z5% (Fig. 3A, B), indicating that a non-receptor-independent mechanism contributed to macrophage LDL uptake, as reported by others (13,14). In contrast, increasing AcLDL concentration up to 50 mg/ml rapidly increased cellular cholesterol, which plateaued at a 3-fold increase, and was accompanied by an increase in cholesteryl ester to z40% (Fig.…”
Section: Cholesterol Traffic In Macrophagessupporting
confidence: 60%
See 1 more Smart Citation
“…Increasing LDL concentration resulted in a linear and nonsaturating increase in uptake, which at 250 mg/ml doubled total cellular cholesterol and increased cholesteryl ester level to z5% (Fig. 3A, B), indicating that a non-receptor-independent mechanism contributed to macrophage LDL uptake, as reported by others (13,14). In contrast, increasing AcLDL concentration up to 50 mg/ml rapidly increased cellular cholesterol, which plateaued at a 3-fold increase, and was accompanied by an increase in cholesteryl ester to z40% (Fig.…”
Section: Cholesterol Traffic In Macrophagessupporting
confidence: 60%
“…The cell can also export excess cholesterol to appropriate extracellular acceptors by transfer mechanisms through cholesterol gradients that involve mostly HDL, mediated via scavenger receptor class B type I (SR-BI) (4) and the ABCG1/G4 transporter (5,6) or the apolipoprotein A-I (apoA-I)-mediated pathway that operates through ABCA1 (7)(8)(9)(10). In addition to the canonical receptor pathway for regulated LDL uptake by the LDL receptor (LDLr) (11,12), the macrophage can take up LDL via receptor-independent pathways, such as macropinocytosis, which, in a dosedependent manner, can lead to macrophage foam cell formation under certain conditions in vitro (13)(14)(15).…”
mentioning
confidence: 99%
“…It has been recently postulated, however, that nLDL plays a role in the accumulation of cholesterol in macrophages independent of the LDL receptor's activity, particularly when cells are stimulated with, for example, inflammatory cytokines. Kruth, et al reported that the stimulation of human monocyte/macrophages with PMA resulted in the accumulation of cholesterol from nLDL, and that this pathway is involved in macropinocytosis 37) . From these observations, we speculate that the EL on macrophages acts as a molecular bridge between circulating nLDL and macrophages in blood vessel walls, and promotes the uptake of LDL by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The radioactivity and protein content of the cell lysate was measured in the same aliquot. Cell-free wells were incubated with [ 3 H]sucrose in parallel incubations and gave a background count less than 5% of the [ 3 H]sucrose radioactivity detected in macrophages (44).…”
Section: Cell Culture Studiesmentioning
confidence: 99%